2015
DOI: 10.1653/024.098.0249
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Stem Borers of the Colombian Cauca River Valley: Current Pest Status, Biology, and Control

Abstract: Sugarcane stem borers of the genus of Diatraea (Lepidoptera: Crambidae) form a species complex that causes serious economic losses to sugarcane production in the Cauca River Valley and other regions of Colombia. Two primary species, Diatraea saccharalis (F.) and D. indigenella Dyar and Heinrich, have been effectively managed for more than 4 decades through augmentative releases of the tachinid flies Lydella minense (Townsend) and Billaea claripalpis (Wulp) (Diptera: Tachinidae) and the egg parasitoid Trichogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 34 publications
1
40
0
11
Order By: Relevance
“…(Lepdoptera: Crambidae), is a major pest of sugarcane in the American continent (Posey et al, 2006;DinardoMiranda, 2008;Vargas;Gómez;Michaud, 2015). Early-instar larvae feed on the leaf parenchyma and leafsheaths while older larvae bore into the stalks reducing sucrose content and weight and facilitating colonization by fungi that causes red rot disease, which indirectly reduce the yield and quality of sugar and ethanol (Long;Macedo;Botelho, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Lepdoptera: Crambidae), is a major pest of sugarcane in the American continent (Posey et al, 2006;DinardoMiranda, 2008;Vargas;Gómez;Michaud, 2015). Early-instar larvae feed on the leaf parenchyma and leafsheaths while older larvae bore into the stalks reducing sucrose content and weight and facilitating colonization by fungi that causes red rot disease, which indirectly reduce the yield and quality of sugar and ethanol (Long;Macedo;Botelho, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Early-instar larvae feed on the leaf parenchyma and leafsheaths while older larvae bore into the stalks reducing sucrose content and weight and facilitating colonization by fungi that causes red rot disease, which indirectly reduce the yield and quality of sugar and ethanol (Long;Macedo;Botelho, 1988). The use of sugarcane cultivars more resistant to D. saccharalis is essential for the Integrated Pest Management of this pest as it emerges as an economically and environmentally effective control measure (Milligan;Balzarini;White, 2003;Posey et al, 2006;Dinardo-Miranda, 2008;Vargas;Gómez;Michaud, 2015). PIMENTEL, G. V. et al Some studies have identified resistance traits in sugarcane cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Increased occurrence of B. claripalpis coincided with population peaks of D. saccharalis. This parasitoid is an important natural enemy of sugarcane borer, and is used on a commercial scale in other Latin American countries, alone or in association with other parasitoids, through mass releases (Vargas et al 2015;Rivera-Escobar & Soto Giraldo 2017).…”
Section: Discussionmentioning
confidence: 99%
“…el daño de observa en las galerías formadas por el insecto. Luego el insecto empupa en el mismo tallo para dar paso a la emergencia del estado adulto, que es una polilla de hábito nocturno y que deposita sus huevos especialmente en el envés de las hojas de la caña (Vargas et al 2015a). Estos mismos autores señalan que el efecto de la plaga en la pérdida de peso del cultivo puede llegar a ser de 0,83 % por cada unidad porcentual de entrenudos barrenados.…”
unclassified
“…Es de señalar que no existen referencias acerca de la dinámica poblacional del complejo de especies de Diatraea presente en el valle del río Cauca con relación a la edad del cultivo de la caña de azúcar. Al respecto, Vargas et al (2015a) observaron que la oviposición de D. indigenella es muy escasa en campos con edades inferiores a los seis meses de edad mientras que se incrementa a partir de los siete meses, lo que coincide con una mayor población de larvas de D. indigenella a partir de este periodo y que contrasta con una mayor población de larvas de D. saccharalis en edades inferiores y que disminuye al avanzar la madurez del cultivo (Gómez y Vargas 2014). Sin embargo, estos autores no brindan información acerca del comportamiento de D. tabernella y/o D. busckella, causantes del brote de la plaga en la actualidad.…”
unclassified